Introduction to Sociological Theory - Miller-Bernal, L. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The ASA Resource Book for Teaching Sociological Theory organizes 24 syllabi and supplemental material for both undergraduate and graduate courses. Each syllabus is introduced in order to give the reader a sense of the institutional context and the pedagogical principles that shaped the creation of the course. For the undergraduate level, there are syllabi covering classical theory, modern theory, and single course combinations. With each syllabi introduced by an instructor’s comment on the context, goals, content, and pedagogy that inform the syllabus, the reader is better enabled to find models of syllabi appropriate to their teaching circumstances. Submissions for this volume come from a variety of schools ranging in size from under 600 to over 30,000 students. The theory syllabi in this volume have a heavy expectation for student performance and evaluation. All courses, graduate and undergraduate, have a serious writing component. All courses emphasize student participation. Most courses attempt to hold students responsible for course readings through periodic examinations. Every syllabus in this volume offers a schedule of weekly or class-by-class topics, readings and assignments.